PEMBENTUKAN SIKAP KONSUMEN YANG DIPENGARUHI OLEH KEBIJAKAN DISTRIBUSI DAN KEBIJAKAN PROMOSI (Studi Kasus Pada Produk Roti Unyil Venus di Kota Bogor) - Jenab, Siti; Maulana, Lucky Hikmat (JURNAL VISIONIDA, 2016)
The aim of this research is to figure out the influence of distribution and promotion policies toward the consumer attitudes establishment of bakery products Roti Unyil Venus in Bogor both simultaneously and partially. Populations of these studies are consumers of Roti Unyil Venus. Samples are taken from 45 respondents using the random sampling method. Data are collected by questionnaires, instrumentt test method is using validity, reliability and classical assumption method, while the data analysis method is using multiple regression analysis, correlation analysis, coefficient of determination analysis and statistical test (F test and t test). Based on the results of multiple regression analysis by F test, distribution and promotion policy show a positive and significant impact on the establishment of consumer attitudes at Roti Unyil Venus simultaniously. The t test shows that distribution and promotion policy partially remain a positive and significant impact on the establishment of consumer attitudes at Roti Unyil.Keywords: Distribution Policy, Promotion Policy, Consumer Attitudes.